2008
DOI: 10.1101/gad.481408
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila HP1c isoform interacts with the zinc-finger proteins WOC and Relative-of-WOC to regulate gene expression

Abstract: Heterochromatin protein 1 (HP1) proteins are conserved in eukaryotes, with most species containing several isoforms. Based on the properties of Drosophila HP1a, it was proposed that HP1s bind H3K9me2,3 and recruit factors involved in heterochromatin assembly and silencing. Yet, it is unclear whether this general picture applies to all HP1 isoforms and functional contexts. Here, we report that Drosophila HP1c regulates gene expression, as (1) it localizes to active chromatin domains, where it extensively coloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
129
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(138 citation statements)
references
References 48 publications
6
129
2
1
Order By: Relevance
“…We and others previously reported that dHP1c interacts with the transcription factors WOC and ROW 17,18 . Here to identify partners of the dHP1c complex, we performed affinity purifications using stable S2 cell lines expressing ROW-TAP and TAP-WOC fused proteins.…”
mentioning
confidence: 70%
See 4 more Smart Citations
“…We and others previously reported that dHP1c interacts with the transcription factors WOC and ROW 17,18 . Here to identify partners of the dHP1c complex, we performed affinity purifications using stable S2 cell lines expressing ROW-TAP and TAP-WOC fused proteins.…”
mentioning
confidence: 70%
“…5c). On the other hand, binding of the dHP1c complex likely involves the recognition of specific DNA sequences since it depends on the zinc-finger proteins WOC and ROW 18 ( Supplementary Fig. 3a,b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations